PENERAPAN DIVERSI DALAM PENYELESAIAN TINDAK PIDANA YANG DILAKUKAN OLEH ANAK DI PENGADILAN NEGERI PEKANBARU - Manurung, Demi; Firdaus, Emilda; Effendi, Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Children who are in the prison environment facing exclusive environment, hanging out with inmates with different types of crime and if free will have a difficult stigma brat rehabilitated throughout his life. One solution that can be used is the implementation of the diversion. Diversion efforts as mandated by the Act to be given to the level of investigation, prosecution and court proceedings, the officer or officers who violate these provisions will be subject to administrative sanctions and criminal penalties. The purpose of this thesis, namely:First, Application Diversion in the completion of criminal offenses committed by children in Pekanbaru District Court, Second, constraints in the implementation of the settlement Diversion criminal offenses committed by children in Pekanbaru District Court, Third, efforts are being made to overcome constraints in the implementation of the settlement Diversion criminal offenses committed by children in the District Court of Pekanbaru. This type of research can be classified into types of sociological research. This type of research is descriptive analysis. Source of data used were obtained through three (3) legal materials are the primary legal materials, secondary and tertiary. The data collection techniques were performed using two methods : interviews and review of the literature. From the results of research and there are three main things that can be inferred. First, Application of diversion in the completion of criminal offenses committed by children in the District Court of Pekanbaru is still not going well because of the lack of understanding of the concept of diversion on the part of law enforcement and the community espspecially the victim's family. Second, constraints in the implementation of the settlement Diversion criminal offenses committed by children in Pekanbaru District Court, law enforcement factors still difficulties in implementing the diversion of children criminals. Third, efforts to overcome obstacles to do in application against crime diversion in progress conducted by Children In Pekanbaru District Court that law enforcement officials, especially the police have to make a special team has been trained in dealing with issues concerning children. Suggestions, First, law enforcement officials should be equipped with knowledge of child protection. Second, provide law enforcement with the knowledge of the importance of the protection of the child's future as the next generation. Third, the government should be more serious in dealing with the problems of children with and more assertive in providing sanctions for ignoring the law enforcement mandate of the Act and need special attention from parents to improve the spiritual education of the child.Keywords : Application - Diversion - Crime – Children